2013
DOI: 10.7314/apjcp.2013.14.7.4409
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Pancreatic Cancer Risk: A Revisit with an Assessment of the Nicotine Dependence Phenotype

Abstract: Background: Cigarette smoking is a well-established risk factor of pancreatic cancer (PC). Although an association between nicotine dependence phenotype, namely time to first cigarette (TTFC) after waking, and the risk of several smoking-related cancers has been reported, an association between TTFC and PC risk has not been reported. We assessed the impact of smoking behavior, particularly TTFC, on PC risk in a Japanese population. Materials and Methods: We conducted a case-control study using 341 PC and 1,705… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cigarette smoking is widely known as a risk factor of pancreatic cancer in Japanese studies (p<0.001) (Lin et al, 2002;Matsuo et al, 2011;Nakao et al, 2013). Another study in Turkey confirmed this related between smoking and pancreatic cancer (p<0.0001) ( Engin et al, 2012) and according to a study in Iran, too.…”
Section: Discussionmentioning
confidence: 89%
“…Cigarette smoking is widely known as a risk factor of pancreatic cancer in Japanese studies (p<0.001) (Lin et al, 2002;Matsuo et al, 2011;Nakao et al, 2013). Another study in Turkey confirmed this related between smoking and pancreatic cancer (p<0.0001) ( Engin et al, 2012) and according to a study in Iran, too.…”
Section: Discussionmentioning
confidence: 89%
“…Epidemiological studies have provided strong evidence that tobacco smoke increases the risk of pancreatic cancer in a dose and exposure-dependent manner [ 4 , 5 , 6 , 7 ]; in a meta-analysis of tobacco risk and pancreatic cancer from 82 studies, there was an estimated 75% increased risk for pancreatic cancer in smokers versus non-smokers. While smoking cessation can lower this risk by up to 50%, the overall risk compared to non-smokers remains elevated in former smokers for up to 10 years or more [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant male/female differences also were found in a hospital-based study conducted in Texas [27]. Clinic-based studies conducted in the U.S. [28] and Japan [29] found increased ORs for current cigarette smoking using friends/spouses, or non-cancer, outpatient controls at the hospitals. One Italian, hospital-based, case-control study found similar ORs(OR=1.3) for former and current smokers [30].…”
Section: Discussionmentioning
confidence: 78%
“…Most epidemiologic studies, using multiple study designs, have demonstrated that heavy smoking(≥20 pack years) is associated with PC [7,8,10,29] and smoking cessation reduces the risk to background levels, particularly after 20 years [7][8][9][10]33]. With a significant decline in cigarette smoking in the US and California in particular over the past decades [54], future research should more fully investigate the degree to which lighter smoking patterns contribute to PC incidence.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 94%